2003
DOI: 10.1074/jbc.m302044200
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Menin, the Product of the Multiple Endocrine Neoplasia Type 1 Gene, Inhibits the Commitment of Multipotential Mesenchymal Stem Cells into the Osteoblast Lineage

Abstract: The physiological roles of menin, the product of the multiple endocrine neoplasia type 1 gene, are not known. Homozygous menin knockout mice exhibit cranial and facial hypoplasia. We, therefore, investigated the role of menin in the regulation of osteoblastic differ-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
88
0
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 56 publications
11
88
0
8
Order By: Relevance
“…As we reported previously (14), ALP activity increases with time, and the expression of type 1 collagen and osteopontin peaks at 7 and 14 days of culture, respectively, whereas mRNA expression of OCN, a terminal differentiation marker, is highest at day 21 of culture. The levels of Tmem119 mRNA increased for up to 2 weeks, and the level was maintained up to week 3 in MC3T3-E1 cells (Fig.…”
Section: Tmem119 Expression During Osteoblast Differentiation-supporting
confidence: 83%
See 2 more Smart Citations
“…As we reported previously (14), ALP activity increases with time, and the expression of type 1 collagen and osteopontin peaks at 7 and 14 days of culture, respectively, whereas mRNA expression of OCN, a terminal differentiation marker, is highest at day 21 of culture. The levels of Tmem119 mRNA increased for up to 2 weeks, and the level was maintained up to week 3 in MC3T3-E1 cells (Fig.…”
Section: Tmem119 Expression During Osteoblast Differentiation-supporting
confidence: 83%
“…Transient or Stable Transfection-Each vector was transfected into MC3T3-E1, ST-2, COS-7, or C2C12 cells with Lipofectamine (Invitrogen) as described previously (13)(14)(15). Six h later, the cells were fed fresh ␣-MEM containing 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the precise biochemical function of menin in this complex needs to be elucidated, the importance of menin in this complex is apparent from the observation that the loss of menin results in reduced H3K4 methylation and associated reduction in the expression of known mixed lineage leukemia targets Hoxc6 and Hoxc8 (6). Interaction of menin with Smad3 is reported to result in activation of transforming growth factor-h (TGF-h)-induced transcription (8), and the interaction of menin with Smad1, Smad3, Smad5, and Runx2 may participate in the TGF-hmediated and bone morphogenetic protein-2 -mediated pathways of commitment of multipotential mesenchymal stem cells to osteoblast lineage (9)(10)(11). Previous studies of gene expression in tumors, cell lines, and embryos have identified nonoverlapping sets of gene(s), whose expression is affected by menin (5,12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have aimed to elucidate menin's function, primarily through investigating its molecular interactions (for a review see Poisson et al, 2003). Menin binds to a variety of transcription factors (Heppner et al, 2001;Kaji et al, 2001;Chandrasekharappa and Teh, 2003;Sowa et al, 2003). It has been found to repress JunD-activated transcription (Gobl et al, 1999;Kim et al, 2003), revealing that, when deprived of menin, JunD switches from growth suppressor to growth promoter (Agarwal et al, 2003).…”
Section: Introductionmentioning
confidence: 99%